Thermal Decomposition Behaviour of Mg(II) and Zn(II) Complexes of cis-2,6-diphenyl-3-ethyoxycarbonylpiperidin-4-one - Manimekali, A.; Mahendhiran, R. (Asian Journal of Chemistry, 2010)
The TG-DTA and IR spectral analysis of complexes of Mg(II)and Zn(II) with cis-2,6-diphenyl-3-ethoxycarbonylpiperidin-4-onewas investigated. The results from thermal analysis have shown thatmainly two step decomposition occured in both the complexes.Various kinetic and thermodynamic parameters for these steps wereestimated employing Horowitz-Metzger and Coats-Redfern methods.